1971
DOI: 10.1159/000211811
|View full text |Cite
|
Sign up to set email alerts
|

Age Changes in the Human Kidney of the Different Races

Abstract: Comparative study has been made histologically and micrometrically on the senile changes of the kidney between Caucasians and Japanese. In both races, weight loss of the kidney, decrease in number of the parenchymal cells and tendency to increase in size of the cells were considered to be main characteristics of the senile changes, but in the process of the senile changes some differences were noticed between the two races. The race differences may be partly due to the difference in the process of sclerotic ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
2
3

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(61 citation statements)
references
References 0 publications
5
49
2
3
Order By: Relevance
“…However, because there were only a few subjects over age 60 and none over age 65, we cannot exclude a decline after age 60. The effect of age on renal parenchymal volume has not been determined in normal individuals, and the results of sonographic or autopsy studies of total renal mass are variable, ranging from a linear decline after age 40 (30) to no decline (20). Measurements of total volume or weight can be misleading in this regard, because sinus fat increases with age (28) and, as shown in this study, varies inversely with parenchymal volume.…”
Section: Discussionmentioning
confidence: 66%
“…However, because there were only a few subjects over age 60 and none over age 65, we cannot exclude a decline after age 60. The effect of age on renal parenchymal volume has not been determined in normal individuals, and the results of sonographic or autopsy studies of total renal mass are variable, ranging from a linear decline after age 40 (30) to no decline (20). Measurements of total volume or weight can be misleading in this regard, because sinus fat increases with age (28) and, as shown in this study, varies inversely with parenchymal volume.…”
Section: Discussionmentioning
confidence: 66%
“…Evidence from autopsy studies suggests a wide range in the number of nephrons in the 'normal' kidney Nyengaard & Bendtsen, 1992). Nephrons are lost both with ageing (Moore, 1931;Nyengaard & Bendtsen, 1992;Tauchi, Tsuboi, & Okutomi, 1971) and due to a variety of nephropathic insults. Damage to the glomerulus, the filtration segment of the nephron, is marked by protein leakage into the urine, making the appearance of urinary protein or albumin a marker of early renal disease.…”
Section: Early Development Explanationsmentioning
confidence: 99%
“…After 40, there was a steady loss of nephrons. Tauchi et al 20 examined the kidneys of Japanese and Caucasians and reported a decrease in the number of parenchymal cells and tendency to increase in the size of cells as the main characteristics of senile changes. The size of glomeruli did not show any marked change with age in Caucasians, whereas in Japanese, there a significant decrease was evident in their size.…”
Section: Discussionmentioning
confidence: 99%